PW 0940 Epidemiology of non-fatal injuries among community members of mbarara municipality, uganda. (November 2018) - Nuwematsiko, Rebecca; Kisakye, Angela; Musoke, David; Oporia, Frederick; Paichadze, Nino; Pariyo, George; Bachani, Abdulgafoor; Kobusingye, Olive; Mugwanya, Kenneth; Ssempebwa, John
Abstract : The burden of injuries in Uganda is poorly quantified with most of the data reported being facility-based and fatal driven. Fatal injuries only represent a small portion of the problem; many non-fatal injuries remain unreported in the communities. This study assessed the prevalence of non-fatal injuries and associated factors among community members of Mbarara municipality, Western Uganda. Between May-June 2017 we conducted a cross-sectional survey among 966 household members. The most recent non-fatal injury (within a six months recall period) that led to the loss of at least one day from normal activity was the non-fatal injury considered for this study. Descriptive statistical analysis was done to estimate the counts and frequencies of non-fatal injuries by socio-demographic and injury characteristics. Modified Poisson regression model was used to determine factors associated with non-fatal injuries. The prevalence of non-fatal injuries among community members was 18.2% with 92% of the injuries being unintentional. Falls (27.3%) were the most common cause of injury followed by road traffic injuries (26.7%). Age (16–25 years) (Adj.PR=0.60 95% CI: 0.37, 0.99), urban residency (Adj.PR=1.50, 95% CI: 1.13, 1.99), non-area tribe, (Adj.PR=2.35, 95% CI: 1.60, 3.46), and being a casual laborer (Adj.PR=2.10, 95% CI: 1.17, 3.77) were independently associated with non-fatal injury. The prevalence of non-fatal injuries in the past six months was high in Mbarara Municipality; this was largely as a result of falls and affecting casual laborers. Therefore more effort is needed to reduce non-fatal injuries such as those resulting from falls in the communities so as to improve the quality of life.